When did the options market in Enron lose its' smirk? - Bruce Mizrach (Rutgers University, Department of Economics, 2002)
The Enron Corporation went from a 65 billion dollar market capitalization to bankruptcy in just 16 months. Using statistical techniques for extracting the implied probability distributions built into option prices, I examine the market's expectation of Enron's risk of collapse. I find that the smart money remained far too optimistic about the stock until just weeks before their bankruptcy filing.
Keywords: G13; 330; Enron; implied probability distributions; options; Insolvenz; Optionsgeschäft; USA; Statistische Verteilung